Molecular Dynamics Study of Structural Properties in a Strongly Coupled One-Component Plasma using Lammps (Lafia Journal of Scientific and Industrial Research, 2026)
The study uses molecular dynamics simulations with LAMMPS to examine a model liquid plasma system which exhibits structural and dynamical properties of a strongly coupled Yukawa-type One-Component Plasma. The phase behavior is methodically investigated over a broad range of coupling strengths., requirements for screening bridging the gap between crystalline solids and weakly coupled gaseous plasmas. The study uses three techniques which include phase space diagrams, Mean Squared Displacement and Radial Distribution Functions to trace the changes which occur throughout the system. The results demonstrate an explicit shift from a disordered gas-like state which occurs at low coupling to a liquid state which has strong short-range order (20.0 ≤ Γ ≤100.0), and ultimately a solid-like state which has crystalline properties at extremely high coupling. The analysis method called "Structural Order vs. Coupling Strength" measures structural order through the first peak height in the RDF which shows a direct relationship with Γ as it increases. The dynamic MSD studies demonstrate that local structure development in RDFs occurs together with caged particle movement initiation while system coupling advancement leads to reduced diffusion rates. The research provides a strong computational system which scientists use to study liquid plasma systems and it enables them to identify phase transitions and study atomic-scale structures and analyze material behavior under extreme conditions. The research results provide crucial support for developing theoretical models which scientists use to study astrophysical plasma systems and inertial confinement fusion, high-energy-density physics because understanding dense plasma states requires knowledge of strongly coupled systems.
Keywords: LAMMPS; M D Simulations; MSD/RDF; strongly coupled; Yukawa-type One-Component Plasma (OCP)